Localized Darier disease: three cases of Type 1 segmental mosaicism. (1st January 2022) - Phillips, D.; Gumparthy, K.; Farrar, C. W.; Karumanchery, R; Tan, B. B.
Abstract: Darier disease (DD) is an autosomal dominant acantholytic dermatosis with an estimated prevalence of 1 in 30 000–100 000. A localized form of DD was first described by Kreibich in 1906 and is thought to account for 10% of all cases. A number of clinical variants have been reported including: unilateral, linear, segmental or zosteriform DD. We present a case series of three patients with localized DD.